2019
DOI: 10.1021/acsami.9b10787
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Transferrin-Modified Porous Silicon Nanoparticles for Targeted Delivery of Doxorubicin to Glioblastoma

Abstract: There is a dire need to develop more effective therapeutics to combat brain cancer such as glioblastoma multiforme (GBM). An ideal treatment is expected to target deliver chemotherapeutics to glioma cells across the blood–brain barrier (BBB). The overexpression of transferrin (Tf) receptor (TfR) on the BBB and the GBM cell surfaces but not on the surrounding cells renders TfR a promising target. While porous silicon nanoparticles (pSiNPs) have been intensely studied as a delivery vehicle due to their high bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 61 publications
2
81
0
Order By: Relevance
“…Unlike Tf, BSA is an inert protein abundantly present in serum and it is reported that BSA modification did not enhance NP uptake via clathrin-mediated receptor-mediated endocytosis 34 . This explains that the uptake was apparently slower as detailed in our previous work 35 . Additionally, the internalisation of Tf@pSiNP in U87 cells was confirmed by means of cryo-TEM imaging ( Fig.…”
Section: Tf Modification On Psinp Enhanced Cellular Uptake By Gbm Celsupporting
confidence: 65%
See 4 more Smart Citations
“…Unlike Tf, BSA is an inert protein abundantly present in serum and it is reported that BSA modification did not enhance NP uptake via clathrin-mediated receptor-mediated endocytosis 34 . This explains that the uptake was apparently slower as detailed in our previous work 35 . Additionally, the internalisation of Tf@pSiNP in U87 cells was confirmed by means of cryo-TEM imaging ( Fig.…”
Section: Tf Modification On Psinp Enhanced Cellular Uptake By Gbm Celsupporting
confidence: 65%
“…As predicted, Tf@pSiNP were non-toxic and did not reduce ATP amount in GBM cells, in agreement to other pSiNP studies in vitro and in vivo 23,51 . In a separate study, we also showed that Tf@pSiNP is also highly tolerable in human cerebral microvascular cells, and non-CNS keratinocytes over a wide range of concentration 35 , highlighting the biocompatibility of those nanoparticles. Since the cells exposed to Tf alone were also highly viable, the amount of Fe 2+ released from Tf did not cause detrimental effects such as ferroptosis 52 .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations